Phylogenomic Synteny Network Analysis of MADS-Box Transcription Factor Genes Reveals Lineage-Specific Transpositions, Ancient Tandem Duplications, and Deep Positional Conservation. Issue 6 (5th June 2017) - Zhao, Tao; Holmer, Rens; de Bruijn, Suzanne; Angenent, Gerco C.; van den Burg, Harrold A.; Schranz, M. Eric
Abstract : Synteny-based network analyses provide new insight into the evolution of the MADS-box gene family. Abstract: Conserved genomic context provides critical information for comparative evolutionary analysis. With the increase in numbers of sequenced plant genomes, synteny analysis can provide new insights into gene family evolution. Here, we exploit a network analysis approach to organize and interpret massive pairwise syntenic relationships. Specifically, we analyzed synteny networks of the MADS-box transcription factor gene family using 51 completed plant genomes. In combination with phylogenetic profiling, several novel evolutionary patterns were inferred and visualized from synteny network clusters. We found lineage-specific clusters that derive from transposition events for the regulators of floral development ( APETALA3 and PI ) and flowering time ( FLC ) in the Brassicales and for the regulators of root development ( AGL17 ) in Poales. We also identified two large gene clusters that jointly encompass many key phenotypic regulatory Type II MADS-box gene clades ( SEP1, SQUA, TM8, SEP3, FLC, AGL6, and TM3 ). Gene clustering and gene trees support the idea that these genes are derived from an ancient tandem gene duplication that likely predates the radiation of the seed plants and then expanded by subsequent polyploidy events. We also identified angiosperm-wide conservation of synteny of several other less studied clades. Combined, these findings provide new hypotheses for the genomic origins, biological conservation, and divergence of MADS-box gene family members.